A Review on Tabernaemontana spp.: Multipotential Medicinal Plant - Athipornchai, Anan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Tabernaemontana is one of the genera that is used in Chinese, Ayurvedic and Thai traditional medicine for the treatment several diseases. From a chemical point of view, the great majority ofÂ TabernaemontanaÂ species have already been subjected to isolation and identification of indole alkaloids present in their several parts. Many of indole alkaloids have been shown to exhibit a wide array of biological activities. The biogenesis, classification and biological activities of the indole alkaloids found in Tabernaemontana species were discussed in this review and its brings the research up-to-date on the bioactive compounds produced by Tabernaemontana species, directly or indirectly related to human health.